1987
DOI: 10.1203/00006450-198707000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Molecular Variants of Growth Hormone in Childhood

Abstract: ABSTRACT. Human growth hormone (hGH) is known to "bioinactive hGH" as a basis for growth failure (13,14). Recent consist of several molecular forms. We examined the mo-improvements in the sensitivity of analytical techniques have lecular nature of circulating hGH in 18 normal children made it possible to achieve that goal. and compared the resulting patterns to those previously obtained in adults. hGH secretion was stimulated with L-MATERIALS A N D METHODS dopa, the hormonal forms were extracted from plasma by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…After a secretory stimulus, the following GH variants appear in plasma: 22 kDa, 20 kDa, one or more not fully characterized 'acidic' forms (deamidated and/or acylated GH), and oligomers composed of these variants (dimeric to pentameric GH) (7,8,33,(36)(37)(38)(39). Oligomers are either non-covalent aggregates (approximately 65 %) or disulphide-linked (approximately 35%) (36,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After a secretory stimulus, the following GH variants appear in plasma: 22 kDa, 20 kDa, one or more not fully characterized 'acidic' forms (deamidated and/or acylated GH), and oligomers composed of these variants (dimeric to pentameric GH) (7,8,33,(36)(37)(38)(39). Oligomers are either non-covalent aggregates (approximately 65 %) or disulphide-linked (approximately 35%) (36,37).…”
mentioning
confidence: 99%
“…Oligomers are either non-covalent aggregates (approximately 65 %) or disulphide-linked (approximately 35%) (36,37). The mixture of GH forms released appears to be independent of the type of stimulus, or the age or sex of the subject (38,39). In addition, 16 kDa, 12 kDa and 30 kDa forms are found in plasma (8), but it is not known whether they are secreted or are fragments derived from peripheral metabolism of GH.…”
mentioning
confidence: 99%
“…1], of which the 22-and the 20-kD variants predominate. The 20-kD molecule has reduced bioactivity and reduced affinity for the GH receptor compared to the 22-kD variant [2,3], It has been demonstrated that the relationship in the circulation be tween the two variants (and some posttranslation-modi fied forms) is the same independently of the form of secre tion (i.e., spontaneous or stimulated), gender, and age [4,5]. This reduces the number of variables contributing to the uncertainty of GH estimates in the individual GH assay.…”
mentioning
confidence: 99%
“…20K and one or more acidic [deamidated and acylated] forms) in plasma shortly after a spontaneous or pharmacologically in duced secretory burst [29,[46][47][48], Their relative propor tions are the same regardless of the secretory stimulus used [49], they are age-and sex-independent. Children secrete the same GH forms as adults [50]. In addition to the monomeric forms just listed, an oligomeric series up to pentameric GH.…”
mentioning
confidence: 99%